MoU signing ceremony between Universiti Teknologi MARA, Malaysia and Quanzhou Vocational and Technical University, China - UiTM Cawangan Kelantan, Unit Komunikasi Korporat (2023)
MACHANG, 18 MAY - UiTM Cawangan Kelantan (UiTMCK) had the privilege of hosting an official international visit from Prof. Yao Dan, Vice President, and Miss Wang Huan, Director of the International Affairs Office, representing Quanzhou Vocational and Technical University (QVTU) in China. The delegation was warmly received by Prof. Dr. Haji Abdol Samad Nawi, the esteemed Rector of UiTMCK, along with Assoc. Prof. Dr. Mohd Nasir Ismail, Deputy Rector of Academic Affairs, Mr. Meer Zhar Farouk Amir Razli, Deputy Rector of Student Affairs, Dr. Norzieha Mustapha, Deputy Rector of Research, Industrial Linkages, and Alumni, as well as the Heads of Faculties at UiTMCK.